Hematopoietic cell transplantation in murine globoid cell leukodystrophy (the twitcher mouse): effects on levels of galactosylceramidase, psychosine, and galactocerebrosides. - Ichioka, T (1987)
Hematopoietic cell transplantation (HCT) prolongs survival in the twitcher mouse, an authentic animal model of human globoid cell leukodystrophy (Krabbe disease; galactosylceramidase deficiency), but the effects of HCT on levels of galactosylceramidase, psychosine, and cerebrosides in the tissues of twitcher mice have not been previously studied. Galactosylceramidase was less than 8% of control activity in tissues of untreated twitcher mice but reached normal values in brain and spleen and 20-30% of control in kidney of 100-day-old twitchers that received HCT at age 10 days. Using a recently developed method for the simultaneous determination of psychosine and cerebrosides, we measured the tissue levels of these lipids in the above animals. The levels of psychosine in brain, sciatic nerve, and kidney of untreated twitcher mice were 44, 200, and 12 times control values, respectively, in 30-day-old animals and 69, 500, and 14 times control levels in 40-day-old mice. On the other hand, levels of cerebroside were approximately 35% of control values in sciatic nerve, remained about the same in the brain, and were elevated 10-fold in the kidney of twitcher mice. After HCT, psychosine levels in the brains of 30-day-old twitchers were lowered to 30-35% of values in untreated twitchers, and the levels remained in that range during the post-HCT period. Similarly, brain cerebroside levels remained low in HCT-treated twitcher mice. Although psychosine levels in sciatic nerves of HCT-treated twitcher mice increased more slowly than in the nerves of untreated twitchers, the levels in 100-day-old HCT-treated twitcher mice had reached the same high values as those seen in untreated 40-day-old twitchers. It is not known whether the extremely high levels of psychosine in sciatic nerves ultimately contribute to the death of twitcher mice after HCT.